(untitled) (Indagatio Didactica, 2025)
Deafness appears to be associated with a decrease in executive functions. Deaf children are perceived and framed more based on their limitations than on their potentialities. Early exposure to spoken or signed language, combined with the development of visual attention, can contribute to greater autonomy and social inclusion of deaf children. The objective of the study is to identify and analyze the main approaches to visual attention in deaf children, from 2000 to 2019. This is a systematic review based on the Scopus and Web of Science databases, highlighting the objectives, instruments used, and conclusions reached. Using a PRISMA table, from 58 studies obtained, 15 articles that met the inclusion criteria were validated for analysis. The analysis was based on age range, reflecting the periods of development of visual attention. The studies converge on the perspective of the development of visual attention in deaf children, going from a period of disadvantage in relation to hearing children in the first years of the child’s life to an improvement after adolescence. Given the frequent difficulty in detecting visual stimuli quickly, we can conclude that early exposure of deaf children to language, whether spoken or signed, produces better results for the development of executive functions than exposure to sound.